The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00436-006-0441-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on Clonorchis sinensis infection in Shenzhen area of Zhujiang delta in China

Abstract: To study the transmission route and epidemiological features of Clonorchis sinensis infection in Shenzhen area, which is the biggest immigration city in the south of China, we examined 1,473 individuals (710 males and 763 females) to assess the current status of C. sinensis infection among the people in a village of Shenzhen in Zhujiang delta of Guangdong province, China. Freshwater snails, 630, of different species known as the first intermediate host of C. sinensis were collected and examined for cercaria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 9 publications
6
23
1
3
Order By: Relevance
“…These species are closely related to C. sinensis infection of the residents in the Pearl River Delta. For this reason, our investigation put emphasis on the infection status of the two kinds of fishes, and its result showed that the mean infection rates of C. idellus and H. nobilis reached 52.42% and 21.65%, respectively, which were higher than those reported by previous studies (Wang et al 2002;Chen et al 1997;Zhang et al 2007). Additionally, the infection rate of C. idellus was higher than that of H. nobilis (χ 2 = 346.2, P<0.005), indicating that the C. idellus was more prone to C. sinensis infection.…”
Section: Discussioncontrasting
confidence: 74%
“…These species are closely related to C. sinensis infection of the residents in the Pearl River Delta. For this reason, our investigation put emphasis on the infection status of the two kinds of fishes, and its result showed that the mean infection rates of C. idellus and H. nobilis reached 52.42% and 21.65%, respectively, which were higher than those reported by previous studies (Wang et al 2002;Chen et al 1997;Zhang et al 2007). Additionally, the infection rate of C. idellus was higher than that of H. nobilis (χ 2 = 346.2, P<0.005), indicating that the C. idellus was more prone to C. sinensis infection.…”
Section: Discussioncontrasting
confidence: 74%
“…The Zhang et al 2007). The release of cercariae from snails is high and occurs over a fairly long period thus ensuring propagation (Keiser and Utzinger 2009;Mas-Coma and Bargues 1997).…”
Section: Clonorchis Sinensismentioning
confidence: 99%
“…C. sinensis metacercariae were collected from fish (Pseudorasbora parva) muscles essentially according to a previously reported method (Zhang et al 2007). Several trematodes infecting humans were included as 'heterologous control samples' for assessing the specificity of the LAMP assay, namely, Opisthorchis viverrini, Fasciola hepatica, Fasciola gigantica, Schistosoma mansoni, and Schistosoma japonicum.…”
Section: Parasitesmentioning
confidence: 99%